Influence of stochastic adhesive porosity and material variability on failure behavior of adhesively bonded composite sandwich joints. (15th February 2023) - Larson, Richard; Bergan, Andrew; Leone, Frank; Kravchenko, Oleksandr G.
Abstract: Progressive damage analysis (PDA) is used to explain experimentally observed differences in failure modes and levels of strength in sandwich panels joined with double lap adhesively bonded joints (ABJ). Experimental data indicates that nominally identical ABJ failed in different failure modes, including facesheet delamination, and a combination of facesheet delamination and doubler net section failure, with joint strengths ranging from 26.8 MPa to 33.3 MPa. A finite element model for the ABJ considers different possible failure modes in the multidirectional facesheet, woven doubler, honeycomb core, and adhesive. PDA predictions by a pristine model agree with the average experimental peak load, strain in the joint, and post-mortem damage states. Material defects are incorporated into an ABJ model that includes simulation of pre-existing matrix damage, local adhesive porosity, and uniform modification of adhesive properties. Analysis of the defect effects suggests existence of structure–property relationships that explain variability in ABJ behavior observed experimentally.